Utility of Neuropathy Screening for Wild-Type Transthyretin Amyloidosis Patients. (21st September 2021) - Russell, Angela; Hahn, Christopher; Chhibber, Sameer; Korngut, Lawrence; Fine, Nowell M.
ABSTRACT: Background: Wild-type transthyretin amyloidosis (wtATTR) is an important cause of heart failure (HF); however, the prevalence and clinical significance of neurologic complications remains uncertain. Methods: This analysis reports findings from a single-centre experience of routine neuropathy screening at the time of wtATTR diagnosis by nerve conduction studies and neurologist assessment, compared with age-matched controls. Results: Forty-one wtATTR patients were included, 39 (95%) males, mean age 78.4 ± 7.7 years, 22 (54%) New York Heart Association (NYHA) class III–IV HF, along with 15 age-matched controls (mean age 77.1 ± 4.2 years, 80% male). Twenty-one (51%) wtATTR patients were diagnosed with polyneuropathy, 15 (37%) with spinal stenosis, 36 (88%) with carpal tunnel syndrome (CTS) and 14 (34%) with ulnar neuropathy. Comparison diagnoses among controls were 1 (7%), 0, 1 (7%) and 3 (20%), respectively. Among patients with NYHA class III–IV HF, 16 (73%) had polyneuropathy compared with 5 (26%) with class I–II (p < 0.01), odds ratio of 7.5 (95% confidence interval 1.9–29.9). After neuropathy screening, 19 (46%) patients were offered neurologic therapy and/or additional diagnostic evaluation. This included CTS release surgery (16, 39%), neuropathic pain medication (3, 7%), nerve block (1, 2%), wrist splinting (2, 5%) and foot care (1, 2%). Spine imaging was performed for 3 (7%) patients, and deltoid muscle and sural nerve biopsy for 1 (2%) patient. Conclusions: Screening of wtATTR patients for neurologic complications resulted in a management change for nearly half. CTS, polyneuropathy and ulnar neuropathy were common. This approach warrants consideration as part of routine assessment for newly diagnosed wtATTR patients.